¿Does alleged consent exist?: the alleged will as underlying justification - Chang Kcomt, Romy Alexandra (2017)
In this paper, the author analyzes the alleged consent, stating their stance against it and proposing, instead, the alleged will, considering that the last is right for describe the legal fiction used to recreate the moment in which the legal holder knows the fact and have the possibility of providing consent to excute the ‘ilicit’ action. In this line, the author reviewed the theories that explain the legal nature of the alleged will, rejecting it as a noncriminal behavior and considering it an autonomous underlying justification. Also, the author describes the requirements of this alleged will, differentiating it from other situations as subrogation. Finally, the author makes a review of the two categories where the alleged will occurs: performances in foreign interest and actions on self-interest.